«Queen of sports» On the way to the XXXIII Olympic games in paris - Mirzoev O.M.; Kalinina O.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the performances of the strongest athletes and sports teams following the results of the 2022 and 2023 World Championships. Methods and structure of the study. The competitive activity of athletes who competed at the 2022 and 2023 World Athletics Championships was analyzed. The results of the unofficial team competition are considered. Results and conclusions. The American team achieved the most victories at world championships - 15 out of 19 possible. The Jamaican national team has lost ground, first of all, we are talking about its male part. Two African teams - Kenyan and Ethiopian - are leaders in middle- and long-distance running and the marathon. As for the teams from Europe, it will be difficult for them to fight for a place in the top five at the Games. As the trend of development of the “queen of sports” in the world shows, track and field athletes (men and women) for the most part “overstepped” the sports results of those who actively trained and performed in the twentieth century.